Industrial Case Study: Cyclone Analysis for Large Scale Calcium Carbonate Looping Process - Zubir M.A.; Manap A.; Afandi N.; Zainuddin R.A.; Hamid M.K.A. (Springer Science and Business Media Deutschland GmbH, 2023)
Carbonation; Coal; Coal fired power plant; Efficiency; Fossil fuel power plants; 750 MWel coal-fired power plant; Calcium carbonate looping; Carbonate looping; Coal-fired power plant; Cyclone analyse; Industrial case study; Inlet pressures; Inlet temperature; Large-scales; Solids distribution; Calcium carbonate